Modul Praktikum Berbasis Projek Pemilah Logam Berdasarkan Berat Termonitoring Iot Berbasis Scada - Hasan Hasan; Irawan Suharto; Medi Yuwono Tharam (Jurnal ELIT, 2023)
Trainer modules based on industrial control operation processes will make it easy for students or learners to understand the concept of using industrial control in real applications. Especially for engineering fields such as electrical engineering, especially the field of industrial automation. To explore the abilities of students more deeply, a module in the research entitled "Scada-Based IoT Monitored Metal Sorting Project-Based Practicum Module" will be designed for a metal sorting process based on weight, whose weight is detected by an analog voltage output load cell sensor as a determinant of the position of placement in the sorting process. The direction of the sorting place is a pneumatic arm that will work according to the detected weight. There are 3 weight categories and 3 containers based on the 3 weight categories. All processes are monitored both from HMI and remotely from Android phones. The results of this study obtained a set of practicum modules that can work as designed and can be monitored by the sorting process through HMI, PC, and cellphone. Monitoring communication can use the access point network, wifi, or cellular telephone network, apart from the embedded HMI wifi network. For communication between PLC and HMI, it still uses Modbus RS-485 communication.